Differential protein phosphorylation in induction of thyroid cell proliferation by thyrotropin, epidermal growth factor, or phorbol ester. - Contor, L (1988)
Protein phosphorylation was studied in primary cultures of thyroid epithelial cells after the addition of different mitogens: thyrotropin (TSH) acting through cyclic AMP, epidermal growth factor (EGF), or 12-O-tetradecanoylphorbol-13-acetate (TPA). EGF or TPA increased the phosphorylation of five common polypeptides. Among these, two 42-kilodalton proteins contained phosphotyrosine and phosphoserine with or without phosphothreonine. Their characteristics suggested that they are similar to the two 42-kilodalton target proteins for tyrosine protein phosphorylation demonstrated in fibroblasts in response to mitogens. No common phosphorylated proteins were detected in TSH-treated cells and in EGF- or TPA-treated cells. The differences in the protein phosphorylation patterns in response to TSH, EGF, and TPA suggested that the newly emerging cyclic AMP-mediated mitogenic pathway is distinct from the better known growth factor- and tumor promoter-induced pathways.